Factores socioambientales y estado nutricional en adultos atendidos en consultorio externo del Hospital III EsSalud Iquitos 2023 - Caja Flores, Lilibeth Yuvitza (2025)
The present study investigated the relationship between socioenvironmental factors and nutritional status in adults treated in the Endocrinology outpatient clinic of Hospital III EsSalud in Iquitos 2023. The objective of the research was to determine the relationship between socio-environmental factors and nutritional status in adults treated at the outpatient Endocrinology clinic. The methodology used the type of quantitative, descriptive, correlational research, and design non-experimental, transversal; The sample was 160 patients seen in the outpatient Endocrinology clinic. The data collection instrument was a record sheet on socio-environmental factors and nutritional status. The relevant results were that: in social factors, 63.1% had a high economic income, 76.2% had a dependent occupation and 69.4% had a degree of higher education; In environmental factors, 76.2% had inadequate food intake, 59.4% had unsanitary housing and 99.4% had no harmful habits; In nutritional status, 86.2% qualified for excess (overweight, obesity); obtaining a significant statistical relationship between nutritional status and economic income (p=0.020), level of education (p=0.034), dietary intake (p=0.001); There was no significance with occupation, type of housing and harmful habits. Concluding that, socio-environmental factors influence the nutritional status of adults who are treated for a health problem in a hospital.